General framework for inverse identification of consecutive parameters - Hrairi, Meftah (IIUM Press, 2011)
The study of inelastic behavior of materials generally follows two steps: (1) the formulation of the mathematical model representing the governing physical effects and (2) the identification of the material's constants. The latter is traditionally achieved through experimental measurements. In this direct identification process, the problem of interpretation of experimental tests requires the assumption of homogeneity of deformation and therefore the use of an approximation method